My Partner Made Me Do It: The Crossover of a Job Incumbent's Job Tension to the Spouse's Workplace Incivility. Issue 4 (8th August 2021) - Thompson, Merideth J.; Carlson, Dawn; Crawford, Wayne S.; Kacmar, K. Michele
ABSTRACT: We propose a spillover-crossover-spillover process model of dual-career couples by which job incumbent job tension contributes to strain-based work-family conflict which motivates their work-based family undermining, that later relates to the spouse's workplace incivility. Further, we propose the spouse's job autonomy moderates the relationship between job incumbent work-based family undermining behaviors and spousal incivility at work. We test the proposed model using a sample of 420 dual-career couples' survey responses collected over three time periods. Results indicate that job incumbent job tension relates positively to their work-based family undermining behaviors, which then associates with the spouse's workplace incivility. These effects are moderated by the spouse's job autonomy such that greater autonomy weakens the relationship between perceived work-based undermining behaviors and incivility at work.